(untitled) (Research, Society and Development, 2025)
This article, based on the master’s dissertation “Blended learning and digital technologies: a case study in an innovative school”, analyzes academic studies – theses and dissertations – carried out in Brazil between 2016 and 2021, focusing on blended learning. The present study aims to consult, systematize and analyze academic productions related to blended learning and digital technologies in Basic Education, enabling a broad and current view of research movements related to the theme. The data collection was carried out through research using the Digital Library of Theses and Dissertations platform and adopts a qualitative approach, of the bibliographic research type, using the State of Knowledge methodology. The selected publications were grouped into three main categories: pedagogical practice, innovation and teacher training. The analysis revealed the need for a broader investigation into the application of the hybrid methodology in all stages of Basic Education, as well as the need to think about teacher training spaces, based on the teacher’s practice, for the use of innovative methodologies. In addition, the importance of proposing teaching alternatives that bring educational spaces closer to the needs of students was highlighted, enabling them to gradually advance towards the role of protagonists in their educational process. It is concluded that this field emerges as a promising area for future research, as it requires the construction of new perspectives on educational processes and on the way of thinking and conceiving the teaching and learning processes.